ANALYSIS OF THE INFLUENCE OF PRODUCT QUALITY AND PRICE ON CONSUMER PURCHASING DECISIONS (MARKETING MANAGEMENT LITERATURE REVIEW) - Cut Mutiarani Fatimah; Laysya Dewiyanda; Salwa Nabila Karsi (Yayasan Wayan Marwan Pulungan, 2025)
This study aims to analyze the influence of product quality and price on consumer purchasing decisions through a literature review in marketing management. The method of writing this scientific article is with qualitative methods and literature review (Library Research). Based on the analysis of previous studies, product quality has been shown to have a significant effect on consumer satisfaction and loyalty, while price functions as an additional factor influencing purchasing decisions, especially for consumers who are sensitive to costs. Both play a role in creating perceived value for consumers. This study concludes that companies need to balance quality and price to influence purchasing decisions effectively.